(untitled) (Bangladesh Journal of Medical Science, 2026)
Background As Kazakhstan grapples with an increasing demand for anesthesia services, particularly in rural and underserved areas, the role of nurse anesthetists emerges as a potential solution to workforce shortages. However, the integration of nurse anesthetists into the national healthcare system remains underdeveloped. Objective This study explores the current role, training pathways, and perceptions surrounding nurse anesthetists in Kazakhstan, with a focus on identifying barriers and opportunities for role expansion. Methods A mixed-methods approach was employed, combining qualitative semi-structured interviews with nurse anesthetists, anesthesiologists, and policymakers, alongside a quantitative survey distributed to 85 healthcare professionals. The study examined perceptions of the role, training experiences, and attitudes toward the integration of nurse anesthetists into anesthesia care. Results The analysis identified four key themes: (1) limited role recognition and utilization, (2) inconsistent training and educational pathways, (3) growing administrative and policy-level support, and (4) mixed professional acceptance. Survey data revealed that 68% of nurses reported insufficient formal anesthesia training, while 72% expressed interest in pursuing specialized nurse anesthetist education. Additionally, 59% of nurses supported expanding the role, but only 34% of anesthesiologists were fully supportive. Regional differences were also noted, with rural areas showing stronger support for the integration of nurse anesthetists. While the role of nurse anesthetists is underutilized in Kazakhstan, there is Conclusion significant interest and growing institutional support for their expanded role. Recommendations include developing standardized training programs, implementing legal reforms, and fostering interprofessional collaboration to ensure safe and effective integration into the anesthesia workforce. BJMS, Vol. 25 No. 02 April’26 Page: 576-582